Measuring The Financial Performance Of Msmes From The Perspective Of Financial Literacy, Financial Inclusion And Financial Technology - Marini Marini; Yusmaniarti Yusmaniarti; Intan Faradilla; Hesti Setiorini (UNIVED Press, 2024)
This research aims to determine the influence of Financial Literacy on the performance of MSMEs in Bengkulu City, the influence of Financial Inclusion on the performance of MSMEs in Bengkulu City, the influence of Financial Technology on the performance of MSMEs in Bengkulu City and the influence of Financial Literacy, Financial Inclusion and Financial Technology on the performance of MSMEs. This research includes associative research. The population in this research is all MSMEs in Bengkulu City, totaling 9 sub-districts. This research uses instrument testing, this research is taken from within the population, the results of which will then be directly used for research. The data analysis technique used is simple linear regression analysis, multiple linear regression. The results of this research show that financial literacy has no effect on the performance of MSMEs in the city of Bengkulu. The T test shows that the financial literacy variable has a calculated t value of -1,369 with a significance level of 0.174. This significance value is greater than 0.05, meaning the first hypothesis is rejected, Financial Inclusion has no effect on the performance of MSMEs. The t test shows that the Financial Inclusion variable has a calculated t value of -0.921 with a significance level of 0.359. This significance value is greater than 0.05, meaning the second hypothesis is rejected, Financial Technology has an effect on MSME Performance. The t test shows that the Financial Technology variable has a calculated t value of 23,021 with a significance level of 0.000. This significance value is smaller than 0.05, meaning that the third hypothesis is accepted.